Polyol-mediated zinc oxide nanoparticles using the refluxing method as an efficient photocatalytic and antimicrobial agent - Walunj, Payal; Roy, Arpita; Jadhav, Vikram; Athare, Pragati; Dhaygude, Akshay; Aher, Jayraj; Algethami, Jari S.; Lokhande, Dnyaneshwar; Alqahtani, Mohammed S.; Bhagare, Arun; Alghamdi, Saad; Eltayeb, Lienda Bashier; et al. (Frontiers in Bioengineering and Biotechnology, 2023)
Nanomaterials have attracted more curiosity recently because of their wide-ranging application in environmental remediation and electronic devices. The current study focuses on zinc oxide nanoparticles’ (ZnO NPs) simple production, characterization, and applications in several fields, including medicinal and photocatalytic degradation of dyes. The non-aqueous-based reflux method is helpful for ZnO NP synthesis; the procedure involves refluxing zinc acetate dihydrate precursor in ethylene glycol for 3 hours in the absence of sodium acetate, in which the refluxing rate and the cooling rate are optimized to get the desired phase, and the unique morphology of polyol-mediated ZnO NPs; it has been achieved using the capping agent TBAB (tetra-butyl ammonium bromide) and precursor zinc acetate dihydrate. UV–Vis, FTIR, XRD, and FESEM structurally characterized polyol-mediated ZnO-NPs. The results show that the material is pure and broadly aggregated into spherical nanoparticles with an average particle size of 18.09 nm. According to XRD analysis, heat annealing made the crystallites more prominent and favored a monocrystalline state. These results and the low cost of making polyol-mediated ZnO NPs demonstrate photocatalytic and antimicrobial properties.